Inhibition of DRP-1-Dependent Mitophagy Promotes Cochlea Hair Cell Senescence and Exacerbates Age-Related Hearing Loss - Lin, Hanqing; Xiong, Hao; Su, Zhongwu; Pang, Jiaqi; Lai, Lan; Zhang, Huasong; Jian, Bingquan; Zhang, Weijian; Zheng, Yiqing (Frontiers in Cellular Neuroscience, 2019)
Background: Mitochondrial dysfunction is considered to contribute to the development of age-related hearing loss (AHL). The regulation of mitochondrial function requires mitochondrial quality control, which includes mitophagy and dynamics. Dynamin-related Protein 1 (DRP-1) is believed to play a central role in this regulation. However, the underlying mechanism of DRP-1 in AHL remains unclear. Here, we examined whether the decline of DRP-1-dependent mitophagy contributes to the development of AHL. Methods: We induced cellular and cochlear senescence using hydrogen peroxide (H2O2) and evaluated the level of senescence through senescence-associated β-galactosidase staining. We evaluated mitophagy levels via fluorescence imaging and Western Blotting of LC3II and P62. Mitochondrial function was assessed by ATP assay, mtDNA assay, and JC-1. Results: We found that both the expression of DRP-1 and the mitophagy level decreased in senescent cells and aged mice. DRP-1 overexpression in HEI-OC1 cells initiated mitophagy and preserved mitochondrial function when exposed to H2O2, while cells with DRP-1 silencing displayed otherwise. Moreover, inhibition of DRP-1 by Mdivi-1 blocked mitophagy and exacerbated hearing loss in aged C57BL/6 mice. Conclusion: These results indicated that DRP-1 initiated mitophagy, eliminated mitochondrial dysfunction, and may protect against oxidative stress-induced senescence. These results provide a potential therapeutic target for AHL.